Electrochemical evidence of the modification of carbon materials with anthraquinone moiety by a Diels Alder process. (20th November 2020) - Deschanels, Mathieu; Favier, Frédéric; Fontaine, Olivier; Vot, Steven Le
Abstract: Interfaces play a key role in electrochemical energy storage. They are directly responsible for performances (and thus indirectly costs), safety and lifetime of the batteries and electrochemical capacitors. A way to improve devices is to control these interfaces and one attractive approach to achieve this goal is to modify electrodes by grafting molecules bearing desired moieties (hydrophilic/hydrophobic, redox…). Diazonium (electro)chemistry is the most popular modification technique in the field of energy storage but it has some limitations. Two major drawbacks are the lack of control on the grafted layer (structure and morphology) and the chemical nature of the diazonium itlself that could, in some cases, makes it difficult to manipulate. Thus, our objective is to propose an alternative option to modify electrodes and, particularly this work aims to validate the use of the Diels Alder reaction to modify carbon materials with redox molecules for electrochemical storage purposes. A new molecule (propargyl anthraquinone) was synthesized to make this Diels Alder reaction possible. The modification was evidenced by electrochemical characterizations, comparing carbon electrodes modified with the synthesized propargyl anthraquinone and other commercial anthraquinone derivatives. The modified carbons were stable in both acidic and buffered neutral conditions and rate capability similar to unmodified carbon. Very interestingly, the electrochemical behavior of our electrodes is comparable to those fabricated by the state-of-the-art diazonium chemistry. In this study, we investigated and validated the possibility to use the Diels Alder reaction to modify carbon for electrochemical storage application. This is a critical input because it allows to expand modification methods suitable to tune interfaces for electrochemical storage applications. Graphical abstract: Image, graphical abstract